Islamic Media Coverage Strategies in Post-Pandemic Hajj Reporting - Setiadi, Anggi Arif Fudin; Ningsih, Ida Nuraini Dewi Kodrat; Prastya, Narayana Mahendra Prastya (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2024)
The Hajj worship in 2022 is the first post-pandemic time for journalists outside Saudi Arabia to report on the Hajj process. This research discusses Islamic media's coverage strategy, which assigns journalists to Saudi Arabia to cover the Hajj. The research utilized a qualitative method with data sources based on interviews with journalists from Republika media, tv Muhammadiyah (tvMu), and NU Online. The research findings reveal that Indonesian journalists can merely cover the Hajj Media Centre of the Indonesian Ministry of Religious Affairs. Another limitation is the prohibition of Saudi Arabian authorities from taking pictures with professional cameras, so journalists employ smartphones to take photos and videos. Regarding news themes, Republika highlighted the importance of health protocols for Indonesian pilgrims. At the same time, NU Online and tvMu reported on religious principles addresed to their respective organizations' perspectives. Primary news sources included pilgrimage officers in Saudi Arabia and Indonesian authorities. In particular, tvMu and NU Online correspondingly interviewed news sources from their respective organizations.